PEMBINAAN MANAJEMEN INTERNET SEHAT DAN AMAN BAGI KELUARGA PADA MASYARAKAT KELURAHAN SEKANAK RAYA - Nora Pitri Nainggolan; Heryenzus; Intan Utna Sari (ASOSIASI IDEBAHASA KEPRI, 2022)
Internet has a positive impact on everyday life, but it can also pose a tremendous threat to families or children. Every parent wants their child not to be trapped into the internet world that tends to be detrimental. Therefore, parents should supervise the activities of children in the internet. This activity was carried out through two meetings, which took place in Sekanak Raya Village where the participants of this devotional activity were the Sekanak Raya community. This devotional activity provides coaching to parents to be able to carry out every stage of managing the use of technology and the internet to be useful in the family including in setting mobile phones so that children cannot open things that are negative, teaching parents to be able to internet healthy with children, teaching parents to be able to supervise children well in the introduction of a healthy internet. Based on the discussion of construction conducted on the Sekanak Raya community, it was concluded as follows: (1).Participants understand about the safe use of smartphones for families; (2).Participants of devotion are able to supervise children in the internet; (3).Participants are able to apply the knowledge obtained in accordance with the material of devotion provided.